Role of immunohistochemistry in gynec oncopathology including specific diagnostic scenarios with associated treatment implications - Bharat Rekhi (Wolters Kluwer Medknow Publications, 2020)
Over the years, immunohistochemistry has emerged as a powerful tool for a more precise diagnosis of certain tumors in gynecologic oncopathology and resolving certain diagnostic dilemmas with significant treatment implications. Certain specific immunohistochemical (IHC) markers have been useful in the more correct identification of rare tumors, characterized by specific molecular signatures. Immunohistochemistry has also been useful in the identification of underlying genetic events, characterizing various tumors, as well as precancerous lesions. This review will focus upon the judicious application of various IHC antibody markers in gynec oncopathology, including authors' experience during "sign-outs" and especially during interaction with other oncology colleagues within the institutional disease management group. The updated references were retrieved from PubMed.